2000
DOI: 10.1103/physrevlett.84.5090
|View full text |Cite
|
Sign up to set email alerts
|

Towards Single-Particle Spectroscopy of Small Metal Clusters

Abstract: We investigate the kinetic-energy spectra of electrons emitted from a metal cluster following laser excitation. This is done in the framework of a coupled ionic and electronic dynamics. Properly chosen laser parameters, leading to gentle excitations, yield kinetic-energy spectra which nicely resolve the multiphoton processes for each occupied state separately. This gives access to the single-particle energies in clusters, provided one works at sufficiently low temperatures and low electron flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 26 publications
4
72
0
Order By: Relevance
“…For multi-photon ionization, the relative proportion of double to single ionization for He, while given much better in approximate TDDFT calculations than in previous calculations assuming a sequential mechanism, still does not show the same pronounced features (the 'knee') seen in experiments [110,111]. The electron spectra from above-threshold ionization have recently been calculated within TDDFT [13,112]. Since the ionization yields and above-threshold ionization spectra depend on probabilities extracted directly from the wavefunction, these errors are suspected to be sins of the wavefunction, mentioned above.…”
Section: Where ∆ (Acc)mentioning
confidence: 99%
“…For multi-photon ionization, the relative proportion of double to single ionization for He, while given much better in approximate TDDFT calculations than in previous calculations assuming a sequential mechanism, still does not show the same pronounced features (the 'knee') seen in experiments [110,111]. The electron spectra from above-threshold ionization have recently been calculated within TDDFT [13,112]. Since the ionization yields and above-threshold ionization spectra depend on probabilities extracted directly from the wavefunction, these errors are suspected to be sins of the wavefunction, mentioned above.…”
Section: Where ∆ (Acc)mentioning
confidence: 99%
“…The upper panel of Fig. 3 shows the PES for the off-resonant case, which is typical for the cluster ground state [13]. The structures corresponding to single-electron hole states 1d, 1p and 1s are well visible.…”
mentioning
confidence: 97%
“…The PES structures and their satellites are strong and can be well discriminated for intensities I = 2 · 10 10 − 2 · 10 11 W/cm 2 . Smaller intensities result in too weak photoelectron yield while higher intensities lead to considerable broadening the PES (see also [13]). The calculations with the fixed intensity I = 10 11 W/cm 2 (as in Figs.…”
mentioning
confidence: 99%
“…This effect was studied for Na clusters in [31] and it was found that the amount of perturbation depends on the strength of the external field. The effect can be quantified in terms of the average number of emitted electrons.…”
Section: Na Clustersmentioning
confidence: 99%